Ultrasensitive and Selective Detection of Cd(II) Using ZnSe‐Xanthan Gum Complex/CNT Modified Electrodes. Issue 5 (7th February 2018) - Ding, Yongling; Hao, Xiaojuan; Yin, Hong; Kyratzis, Ilias Louis; Shen, Shirley; Sun, Kangning; Liu, Futian; Musameh, Mustafa M.
Abstract: This work describes for the first time the employment of water soluble GSH‐ZnSe QDs stabilized by XG and MWCNT for electrode modification in the detection of Cd ions in a highly sensitive and selective manner resulting from the unique structure and surface chemistry of the used QDs. The surface of a glassy carbon (GC) electrode was modified through casting a thin layer of multiwalled carbon nanotubes (MWCNT) followed by a complex layer of ZnSe quantum dots (QDs) stabilized by xanthan gum (XG). Due to the electrocatalytic properties of MWCNT and electroanalytical performance of ZnSe‐XG complex, the new modified electrode significantly improves the sensitivity and selectivity of Cd(II) detection and exhibits enhanced performance in comparison to bare GC, ZnSe/GC and ZnSe/MWCNT/GC electrodes. Strong interactions between ZnSe QDs and XG resulting from hydrogen bonding and complexing association led to stabilization of ZnSe QDs and higher affinity towards Cd(II) ions adsorption compared to a ZnSe QDs film alone. The modified electrode showed linear response in a wide concentration range from 100 nM to 5 μM (R 2 =0.9967) along with a high sensitivity of 156.6 nA ⋅ mol −1  ⋅ L −1 and a low detection limit of 20 nM. The electrode shows high selectivity to Cd with negligible interference from other metal ions and salts. Abstract :